Pendampingan Masyarakat dalam Manajemen Budidaya Tanaman Obat Keluarga di Desa Beringin Kencana, Kecamatan Candipuro, Kabupaten Lampung Selatan - Sari, Yuliana; Muhammad, Hasanuddin; Prayoga, Dian Aji; Bela, Hervi Septa; Khafifah, Suci Nina (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Family medicinal plants (TOGA) or now better known as Family Medicine Gardens are plants that can be cultivated in the yard of the house and have benefits as traditional herbal medicines. The existence of TOGA in the home environment is very important, especially for families who do not have access to health services. In addition, the problem faced by the community in Beringin Kencana Village, Candipuro District, South Lampung Regency, Lampung Province in developing TOGA through the use of their yards is the community's knowledge about the types of plants that are efficacious as medicine. The purpose of this activity is to increase public understanding regarding the utilization yard for making TOGA as an effort to supply family herbal medicines. This service involves the community and KKN students. The methods used in the implementation of community service include elaboration, demonstrations, and the practice of planting TOGA. The result of this planting is that the community not only knows the benefits but also the community is asked to cultivate TOGA so that the community can use it in efforts to maintain health and treat disease. It can be concluded from this activity that the community's knowledge regarding the use of their yards for making TOGA is very good where the community starts making TOGA in their yards.